Seismic Line Disturbance Alters Soil Physical and Chemical Properties Across Boreal Forest and Peatland Soils - Davidson, Scott J.; Goud, Ellie M.; Franklin, Caroline; Nielsen, Scott E.; Strack, Maria (Frontiers in Earth Science, 2020)
Industrial activities for resource extraction have led to a network of seismic lines across Canada’s boreal regions where peatlands often make up over 50% of the landscape. These clearings can have a significant influence on ecosystem functioning through vegetation removal, flattening of microtopography, altering hydrological pathways and impacting biogeochemical processes. Recently, there has been a concerted effort to restore seismic lines to bring back the localized microtopography and encourage ecosystem recovery. A common restoration approach on seismic lines is mounding, which involves using machinery to recreate natural microtopography. Research is scarce on the impact on soil properties following both these disturbances and subsequent restoration on organic soils. The objectives of this study were to 1) identify differences in soil physical and chemical characteristics between areas disturbed by seismic lines and adjacent natural areas, and 2) to determine changes to soil physical and chemical properties following the mounding restoration technique. Research was undertaken at two contrasting boreal ecosites (a poor mesic and a treed fen) near Fort McMurray, Alberta, Canada. In July 2018, we collected soil samples at 34 seismic line locations, both on the line and 20 m into the adjacent undisturbed area. Samples were analyzed for bulk density, volumetric water content (VWC), organic matter content (OM), C:N ratios and δ13C/δ15N isotope analysis. Seismic line disturbances had a significant impact on soil properties, with increased bulk density and VWC on the line at both ecosites. We found an almost 40% reduction in OM on the line compared to natural areas at the poor mesic site, implying changes to carbon cycling, increased mineralization rates and carbon loss from the system. There was also δ13C/δ15N enrichment and narrower C:N ratios on the line, indicating increased decomposition. We found evidence of increased decomposition on the mounds created after restoration at the treed fen. Our results highlight a trade-off between restoration activities that may encourage recovery but also cause increased carbon losses from the system. This research is a first step in gaining a better understanding of these impacts in light of current restoration practices to ensure best management practices for improving ecosystem functioning.